An increase in neural stem cells and olfactory bulb adult neurogenesis improves discrimination of highly similar odorants. (14th January 2019) - Bragado Alonso, Sara; Reinert, Janine K; Marichal, Nicolas; Massalini, Simone; Berninger, Benedikt; Kuner, Thomas; Calegari, Federico
Abstract: Adult neurogenesis is involved in cognitive performance but studies that manipulated this process to improve brain function are scarce. Here, we characterized a genetic mouse model in which neural stem cells (NSC) of the subventricular zone (SVZ) were temporarily expanded by conditional expression of the cell cycle regulators Cdk4/cyclinD1, thus increasing neurogenesis. We found that supernumerary neurons matured and integrated in the olfactory bulb similarly to physiologically generated newborn neurons displaying a correct expression of molecular markers, morphology and electrophysiological activity. Olfactory performance upon increased neurogenesis was unchanged when mice were tested on relatively easy tasks using distinct odor stimuli. In contrast, intriguingly, increasing neurogenesis improved the discrimination ability of mice when challenged with a difficult task using mixtures of highly similar odorants. Together, our study provides a mammalian model to control the expansion of somatic stem cells that can in principle be applied to any tissue for basic research and models of therapy. By applying this to NSC of the SVZ, we highlighted the importance of adult neurogenesis to specifically improve performance in a challenging olfactory task. Synopsis: A transitory expansion of neural stem cells results in an increase in adult born neurons that functionally integrate in the mouse olfactory bulb. These neurons improve the performance of challenging olfactory tasks by increasing the discrimination of similar odorants. A novel mouse model for the inducible and tissue‐specific expression of Cdk4/cyclinD1 (4D) allows the expansion of somatic stem cells. Expansion of neural stem cells in the adult subventricular zone triggers the long‐term increase in adult neurogenesis. Supernumerary neurons can physiologically migrate, mature and integrate in the olfactory bulb circuitry. Mice with increased adult neurogenesis are better specifically at discriminating highly similar odorants. Our mouse model might provide an important tool toward investigating the use of somatic stem cells for recovery of organ function in disease models. Abstract : Surplus olfactory neurons induced in adult mice are not only functionally and morphologically integrated, but can also contribute to enhanced sensory performance on a challenging olfactory task.